TEKNIK SINEMATOGRAFI FILM PENDEK AIR MATA IMPIAN KARYA MULTIMEDIA DARUSSALAM BLOKAGUNG BANYUWANGI - Agus Baihaqi; Khotib Ibrahim (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The main objective of this article is to find out what cinematographic techniques are used in the short film entitled Air Mata Impian by Multimedia Darussalam in terms of cinematographic techniques. This study used a qualitative research method with a qualitative descriptive type. In this study, researchers describe or construct theories that exist in depth on research subjects. In this research, the object of research is to analyze the cinematographic techniques applied in the film Air Mata Impian by MMD. The results of the research in this article show that the cinematographic techniques analyzed include the camera angle formula 5C, close up/shot size, composition, continuity, and cutting. There are 5 cinematographic techniques of Joseph V. Mascelli A.S.C which were also carried out by the Multimedia Darussalam Team in making the short film Air Mata Impian, namely camera angle, close up/shot size, composition, continuity, and cutting/editing.